Strategi Pendayagunaan Zakat Produktif Oleh Badan Amil Zakat Nasional (BAZNAS) Kabupaten Garut Perspektif Hukum Ekonomi Islam - Munir, Ridwan; Abdullah, Muhyi (STAI Al Musaddadiyah Garut, 2022)
The utilization of zakat managed by the Zakat Collector (BAZNAS) is not limited to specific activities based on conventional orientations but can also be used for Shariah-compliant economic activities, such as poverty alleviation and employment creation by providing productive zakat to those in need as business capital. Productive zakat is zakat where the wealth or zakat funds given to the recipients are not spent consumptively. Instead, the zakat funds are provided to recipients to develop a productive business, with implementation continuously supervised and guided by authorities, transforming recipients from beneficiaries to contributors. Especially with the programs created by BAZNAS Garut Regency using appropriate methods will help improve the welfare of the recipients. This study aims to understand the strategies of BAZNAS Garut Regency in utilizing productive zakat from the perspective of Islamic Economics and to determine the implementation of various productive zakat programs in BAZNAS Garut Regency. This research is conducted through field research with a qualitative approach. Data collection techniques include observation, interviews with informants, and documentation. Data analysis techniques involve data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded that BAZNAS Garut Regency's strategy in utilizing productive zakat through the Garut Prosperity program involves using zakat funds as capital for business development. In the implementation of zakat fund utilization, BAZNAS provides supervision, training, and mentoring to the recipients to run their businesses. BAZNAS Garut Regency distributes the Garut Prosperity program's business capital assistance. BAZNAS Garut Regency's strategy in utilizing productive zakat through the Garut Prosperity program has a positive impact on the recipients, especially in the development of their businesses, thus contributing to their economic well-being, albeit slowly, and enabling them to meet their daily needs. Keywords: Strategy, Utilization, Productive Zakat